The Stimulation of Integrative Holistic in Kindergarten (Universitas Negeri Semarang, 2022)
The problem in this study is how to stimulate integrative holistic-based abilities in TK Damhil DWP UNG, Limba U 2 Village, Kota Selatan District, Gorontalo City. The purpose of this study was to determine the Stimulation of Integrative Holistic-Based Ability in Kindergarten. The method used in this study was descriptive qualitative. Data collection techniques using observation techniques, interviews, and documentation. The data analysis technique in this study uses an interactive model of Milles and Hubberman. The results of the research can be observed optimally based on three indicators in integrative holistic learning, namely (1) Connectedness, where the teacher determines and designs the learning activities to be carried out. (2) Inclusion, where children can carry out learning activities according to the direction of the teacher and carry out learning activities without the help of the teacher. (3) Balance, where the teacher provides supervision during learning activities. Keywords: Ability, Children, Holistic, Integrative, Kindergarten